Transcranial direct current stimulation improves time perception in children with ADHD - Vahid Nejati; Fateme Mirikaram; Michael A. Nitsche (Scientific Reports)
Abstract Individuals with ADHD struggle with time perception. The ventromedial prefrontal cortex (vmPFC) and dorsolateral prefrontal cortex (dlPFC) are two distinct cortical areas that are involved in the psychopathology of ADHD, including time perception. In the present study, we aimed to explore if modulation of the excitability of these areas with non-invasive brain stimulation alters time perception in ADHD. Twenty-six children with ADHD performed time discrimination and time estimation/reproduction tasks in five sessions with one week interval and specific tDCS conditions. The tDCS conditions were anodal left dlPFC/cathodal right vmPFC, the reversed electrode positioning, isolated anodal left dlPFC, right vmPFC stimulation with extracranial return electrodes, and sham stimulation. An improved time discrimination was observed in all real stimulation conditions compared to sham stimulation, however the results did not differ between real stimulation conditions. For the time reproduction/estimation task, anodal vmPFC/cathodal dlPFC, isolated anodal dlPFC stimulation and isolated anodal vmPFC stimulation with extracranial return electrodes improved time reproduction, but not estimation, compared to sham stimulation. These results imply that the left dlPFC and right vmPFC are involved in time estimation, whereas the right vmPFC might be more critical for time reproduction. This finding is discussed in light of task and stimulus properties.